Behavioral evidence of the functional interaction between the main and accessory olfactory system suggests a large olfactory system with a high plastic capability - Mier Quesada, Zacnite; Portillo, Wendy; Paredes, Raúl G. (Frontiers in Neuroanatomy, 2023)
Olfaction is fundamental in many species of mammals. In rodents, the integrity of this system is required for the expression of parental and sexual behavior, mate recognition, identification of predators, and finding food. Different anatomical and physiological evidence initially indicated the existence of two anatomically distinct chemosensory systems: The main olfactory system (MOS) and the accessory olfactory system (AOS). It was originally conceived that the MOS detected volatile odorants related to food, giving the animal information about the environment. The AOS, on the other hand, detected non-volatile sexually relevant olfactory cues that influence reproductive behaviors and neuroendocrine functions such as intermale aggression, sexual preference, maternal aggression, pregnancy block (Bruce effect), puberty acceleration (Vandenbergh effect), induction of estrous (Whitten effect) and sexual behavior. Over the last decade, several lines of evidence have demonstrated that although these systems could be anatomically separated, there are neuronal areas in which they are interconnected. Moreover, it is now clear that both the MOS and the AOS process both volatile and no-volatile odorants, indicating that they are also functionally interconnected. In the first part of the review, we will describe the behavioral evidence. In the second part, we will summarize data from our laboratory and other research groups demonstrating that sexual behavior in male and female rodents induces the formation of new neurons that reach the main and accessory olfactory bulbs from the subventricular zone. Three factors are essential for the neurons to reach the AOS and the MOS: The stimulation frequency, the stimulus’s temporal presentation, and the release of opioids induced by sexual behavior. We propose that the AOS and the MOS are part of a large olfactory system with a high plastic capability, which favors the adaptation of species to different environmental signals.